Queer Race Pedagogy in Adult Higher Education: Dealing with Power Dynamics and Positionality of Gay Students of Color - Mitsunori Misawa (Adult Education Research Conference, 2006)
This paper presents a theoretical concept of the intersection of race and sexual orientation and to describe Queer Race Pedagogy (QRP) in adult higher education. This paper provides an overview of racism and heterosexism in adult higher education and the two theories that are utilized to develop QRP.
Keywords: Queer race pedagogy; adult higher education; positionality; power